2011
DOI: 10.4236/fns.2011.24045
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Biochemical and Histological Changes Induced by Zearalenone Mycotoxin on Liver in Male Mice and the Protective Role of Crude Venom Extracted from Jellyfish <i>Cassiopea Andromeda</i>

Abstract: Zearalenone (ZEN) is a non steroidal estrogenic mycotoxin produced by Fusarium species of fungi which contaminate human foods and animal feeds worldwide. In this study hepatotoxicity of ZEN was evaluated in mice by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Albumin levels increased in the experimental animals (Table 2). Al-Seeni et al (2011) also reported a temporary increase in albumin concentrations in zearalenone-induced mycotoxicosis. There are no published references to diseases that are accompanied by increased serum albumin levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Albumin levels increased in the experimental animals (Table 2). Al-Seeni et al (2011) also reported a temporary increase in albumin concentrations in zearalenone-induced mycotoxicosis. There are no published references to diseases that are accompanied by increased serum albumin levels.…”
Section: Discussionmentioning
confidence: 99%
“…There are no published references to diseases that are accompanied by increased serum albumin levels. Elevated albumin concentrations are generally attributed to dehydration resulting from decreased feed or water intake (Al-Seeni et al 2011). In view of the antioxidant properties of albumins and ZEN's ability to induce oxidative stress, an increase in albumin con-centrations could be part of the body's response to disturbance of the oxidative homeostasis (Abid-Essefi et al 2009, Tawerna et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a continuing need exists for the development of reliable methods for the detection of these mycotoxins. A wide range of analytical methods is currently available for this purpose, including high-performance liquid chromatography (HPLC), liquid chromatography-tandem mass spectrometry (LC-MS/MS), thinlayer chromatography (TLC), gas chromatography (GC) and enzyme-linked immunosorbent assays (ELISA) (10)(11)(12)(13). Furthermore, many common detection methods take advantage of the native fluorescence of OTA and ZEN (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…ZEA has been implicated in reproductive disorders, as it can bind and activate estrogenic receptors [ 5 ]. ZEA has also shown multiple toxicities in the immune system [ 6 ], liver [ 7 ], and kidney [ 8 ]. In addition, it has carcinogenic potential [ 9 ] and enhances lipid peroxidation [ 10 ], which are most likely a result of its oxidative stress properties [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%